The Partisan Glade Geosite (Western Greater Caucasus) as an Important Resource and Rising Tourist Attraction - Anna V. Mikhailenko; Dmitry A. Ruban; Svetlana O. Zorina; Fatmeh Tahhan; Konstantin I. Nikashin (Geoconservation Research)
Geoheritage is an important resource for contemporary society, and the inventory of geosites remains an urgent task, especially in geologically rich, but poorly known regions. The present study offers a systematic description of the Partisan Glade geosite, which is a large, elongated locality in the western Greater Caucasus. There, tourist activities have accelerated significantly in the past decade. This geosite represents Lower–Middle Jurassic deep-marine siliciclastics, and it shows Upper Jurassic carbonates, unusual landforms, landslides, and tectonic structures. The geosite is heterogeneous, and it consists of five parts with different properties. The Partisan Glade geosite is important for geological research and education. It can also be employed in geotourism development. The multiple scenic views and fascinating landscape contribute to the importance of this geosite as a rising tourist attraction. Some practical implications concerning conservation and planning issues are specified.